Analysis of Shelf Life and Antibacterial Actvity of Sumbawa Wild Horse Milk against Escherecia Coli and Staphylococcus Aureus Bacteria - Lubis, Novriyanti; Setyaningsih, Baiq Inges; Nuari, Doni Anshar (Department of Technology of Agricultural product (THP) Jambi University, 2023)
Sumbawa wild horse mik is pure milk produced by a mare which is bred in sumbawa and is a healthy drink that has antibacterial activity and longer shelf life duration without using preservatives. This study aims to analyze the shelf life and antibacterial activity of Sumbawa wild horse milk (SWHM) against Escherecia coli and Staphylococcus aureus bacteria, with test parameters including water content, fat content, protein content, pH, and testing was carried out on the 15th day and 30th day after milking and storage at room temperature. The results showed that SWHM did not decay or changes in levels that were far different during the storage period of 15-30 days at room temperature, with the results of fat content of 86.182% and 1.6650%, protein content of 2.1624% and 2.2961%, 86.1821% water content and pH 5.21 and 4.00. Antibacterial activity plays more role in inhibiting Escherichia coli bacteria compared to Staphylococcus aureus with a concentration of 50%, 75%, and 100% with a maximum inhibition of 12.77 mm.